Evaluating BSI Mobile User Satisfaction: The Impact of Product Quality and User Decisions with Islamic Branding as a Moderator - Jamilatul Arrohmah; Kharis Fadlullah Hana (Journal of Finance and Islamic Banking, 2024)
Digital transformation in the banking sector has reshaped customer expectations, necessitating the adoption of mobile banking services. However, despite the increasing number of BSI Mobile users, there is still limited understanding of how product quality and user decisions influence user satisfaction, particularly within the framework of Islamic branding. Existing research on digital banking primarily focuses on service quality and usability, but studies examining the moderating role of Islamic branding in customer satisfaction remain scarce. This study aims to bridge this gap by analyzing the direct and moderated effects of product quality and user decisions on user satisfaction with BSI Mobile. A quantitative approach was employed, collecting data from 100 respondents via a structured questionnaire. Data analysis was conducted using SmartPLS 4 with Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that user decisions negatively impact satisfaction, while product quality positively influences satisfaction. Furthermore, Islamic branding negatively affects satisfaction but positively moderates the relationships between product quality, user decisions, and satisfaction. These insights highlight the need for improved product quality and strategic Islamic branding approaches to enhance digital Islamic banking services and customer engagement.